PENGGUNAAN LEGO SEBAGAI ALTERNATIF PENANAMAN PENDIDIKAN KARAKTER DALAM MEMAHAMKAN KONSEP PENGURANGAN BILANGAN ASLI - Rusmini, Rusmini (Universitas Insan Budi Utomo, 2020)
Mathematics subjects, often unknowingly, clash the teacher in instilling character education. Not infrequently, in the process of learning mathematics, the teacher gives a bad character investment. Call it in the subtraction of natural numbers. Often teachers use the word 'borrow'. In fact, he never returned the loan. Then the purpose of the research conducted with this classroom action research method is to improve the learning process so that it no longer instills bad character. The researcher uses lego media as a model of the enumerator in instilling the concept of subtracting natural numbers. The results obtained that by using lego media, students can reduce natural numbers without making mistakes in concepts and learning outcomes obtained in classical completeness is 84.6%. Through this learning, even the cultivation of bad characters can be eliminated.